PENGARUH PENGENDALIAN BIAYA PRODUKSI TERHADAP PRODUKTIFITAS PERUSAHAAN PADA PT. XYZ - Rudianto Rudianto (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
One of the largest rubber glove companies in North Sumatra experienced fluctuations in the value of productivity and production costs incurred. From the observation of cost data, it was found that the realization of the company's production costs are still fluctuating and not linear to the level of productivity produced. This research aims to find out more about the level productivity and the effect of controlling production costs on these productivity. Measurement of productivity uses the formula of total productivity of input costs, while the method of multiple linear regression analysis is used to determine the coefficient of influence of the three cost variables, so it can be known which production costs are most influential on productivity. The results showed that the level of productivity of the company was good, an average of > 98%. The instability of the productivity level could be caused by factors of performance and availability of production machines. Based on the F test and t test, labor costs have the highest influence value among other production costs (raw material costs, overhead costs). Further research can consider other cost factors that affect the value of company productivity.